Effect of blood pressure on the mortality of the elderly population with (pre)frailty: Results from NHANES 1999–2004 - Li, Menghuan; Su, Zhenyang; Su, Hu; Zuo, Zhi; He, Yuan; Yao, Wenming; Yang, Jiaming; Zhang, Kerui; Wang, Hui; Kong, Xiangqing (Frontiers in Cardiovascular Medicine, 2022)
Backgrounds: The optimal blood pressure is still unclear in elder people with frailty or prefrailty. We aimed to explore the relationship between blood pressure and mortality in the elderly with pre(frailty) Methods: A total of 528 participants aged 60 and older were exacted for analyses of the association between blood pressure and mortality from the database of the National Health and Nutrition Examination Survey (NHANES) (1999–2004). Kaplan–Meier curves and log-rank tests were used to investigate the differences in survival between groups. Multivariate Cox regression and restricted cubic spline analysis were applied to explore the relationship between blood pressure and mortality. Results: During the median follow-up time of 116.5 (interquartile range of 60-186) months, 363 all-cause deaths and 122 cardiac deaths were documented. For all-cause mortality, more participants died with systolic blood pressure (SBP) <110mmHg (Log-rank P=0.030). After adjusting for cofounders, SBP within 110-120mmHg (HR 0.57, 95%CI:0.33-0.98) and 130-140mmHg (HR 0.59, 95%CI:0.36-0.96) had a lower rate of all-cause mortality compared with SBP<110mmHg. There were no significant differences in all-cause mortality among DBP categories. A J-curve association was identified between SBP and hazard ratio for all-cause mortality (P for nonlinear=0.027), with 139.6mmHg as the lowest hazard ratio of all-cause mortality. And for cardiac deaths, a nonlinear relationship was determined between SBP and hazard ratio for cardiac deaths (P for nonlinear=0.025), with 140.1mmHg as the lowest hazard ratio of cardiac deaths. When SBP was higher than 140.1mmHg, each 10mmHg rise in SBP was associated with a 17% increased risk of cardiac deaths (HR 1.17, 95% CI 1.02-1.35). Conclusions: Lower SBP level is associated with higher all-cause mortality in older individuals with pre(frailty). There are J-shaped associations between SBP and mortality, with the optimal SBP around 140mmHg for this population specifically.